Investigating how E-training and E-leadership influence Employee Performance: Testing the Mediation of Work Motivation - Alkashami, Mohamed (CENTRAL ASIA AND THE CAUCASUS, 2021)
Keeping in view the research objectives current study tested the relationship of E- training and E-leadership on employee performance directly and indirectly through work motivation as a mediator. Total seven relationships were proposed. Five direct relationships and two indirect relationships were tested. For testing, the relationships data were collected from 212 bank employees working in the Kingdom of Bahrain. The target sample was selected through simple random sampling, data screening was done through SPSS23 and the model was assessed through structural equation modeling through Smart PLS3. Current research found a significant positive effect between the relationship of E-training, E-leadership towards employee performance, and work motivation. While the effect of work motivation was insignificant factor in predicting employee performance. The current study also found an insignificant mediating effect of work motivation on the relationship between E-training, E-leadership, with employee performance. Furthermore, current research has implications for policymakers and practitioners.